Ojibwe materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Seaman, John Nelson, 1915-; Williams, Angeline; Medler, Andrew; Nakanikan, Dan; Silas, Mrs. John B. (1925)
Several items relating to the Ojibwe (Ojibwa, Chippewa) language have been identified in the C. F. Voegelin Papers. They are located in both Subcollection I and Subcollection II. In Subcollection I, they include relevant correspondence with John N. Seaman (regarding Chippewa fieldwork in Michigan and consultants Mr. Maidler [Medler?] and Charlie David) and a partial letter with Ojibwe text in the Unidentified folder; 6 boxes of Ojibwe notecards, 1 box of Seneca, Ojibwe and Penobscot notecards, and 2 folders of Ojibwe notes (mostly vocabulary and linguistic, but one slip notes addresses of consultants Nicholas Plain of Sarnia and Elijah Pinnance of Walpole Island--there is also, unexpectedly, a bibliography for sources on Arawakan languages at the end of Ojibwa #4) in Series II. comparative vocabularies of Ojibwe and Potawatomi ("Pottowatomi") in Series V. Research Notes Subseries V-A: Language Notes; unbound Eastern Ojibwe texts ("The Walpole Island" and others) in Series V. Research Notes, Subseries V-B: Text; and 24 folders of Ojibwe notebooks in Series VI. Notebooks. Contents of the Blackfoot and Ojibwe notebooks in this series were described in detail by Richard A. Rhodes in 1988. Blackfoot and Ojibwe notebooks are arranged in the order of Rhodes' list, a photocopy of which is filed in the first Blackfoot folder. In general the Ojibwe notebooks are full of vocabulary words and phrases on all kinds of topics, notes on various parts of speech, notes on dialects, texts both with and without English translations, etc. Several consultants are named, of which Angeline Williams is the most prominent [see Odawa entry for more on Angeline Williams]. At least some of these materials appear to be associated with the Linguistic Institute and might be the work of students. Materials in Subcollection II include correspondence with Leonard Bloomfield (letters written in Ojibwe, with some interlinear English translation) and John N. Seaman (regarding field work with Chippewa speakers in Oscoda, Michigan, including Dan ...